THE EFFECT OF CITRA KIRANA BRAND AMBASSADOR ON CONSUMER CONFIDENCE ON KIRANTI’S PRODUCT HOAX INFORMATION IN SOCIAL MEDIA - Melinda Oktaviany; Nawiroh Vera (Metakom, 2019)
This study is the result of quantitative research to test the hypothesis that brand ambassadors Citra Kirana has an effect on the level of consumer confidence inthe hoax information kiranti’s product on social media. Samples in this study were 70 respondents, determining the sample using stratified sampling technique with the criteria of respondents teenage girls in Yadika High School 3. Tests of data analysis using validity, reliability, ANOVA test and simple linear regression test. By looking at the Anova table test there is a P-value at a significant column of large 0,000 <0,005 level of significant meaning that there is an influence between the two variables. it can be concluded that Ha is accepted and Ho is rejected. The results of the determination coefficient (r square) amounted to 0.206 which means that the brand ambassador variable of Citra Kirana was able to increase consumer confidence in the Kiranti product hoax information on social media by 20.6%.Keywords: brand ambassador, public relations, credibility